Research on plants for the understanding of diseases of nuclear and mitochondrial origin - Spampinato, Claudia Patricia (2012)
Different model organisms, such as Escherichia coli, Saccharomyces cerevisiae, Caenorhabditis elegans, Drosophila melanogaster, mouse, cultured human cell lines, among others, were used to study the mechanisms of several human diseases. Since human genes and proteins have been structurally and functionally conserved in plant organisms, the use of plants, especially Arabidopsis thaliana, as a model system to relate molecular defects to clinical disorders has recently increased. Here, we briefly review our current knowledge of human diseases of nuclear and mitochondrial origin and summarize the experimental findings of plant homologs implicated in each process.